Biliary ductal variations and its clinical implications: a cadaveric study - Parmar, Priyanka; Rathee, Suresh Kanta; Dhattarwal, SK; Marwah, Sanjay (International Journal of Research in Medical Sciences, 2017)
Background: Biliary ductal region being frequently abnormal has been the subject of research since long time for anatomists, surgeons and radiologists as well. Methods: The present study was carried out in the department of Anatomy at PGIMS, Rohtak on 50 specimens of liver taken unblock with associated structures. Results: Accessory hepatic and accessory cystic ducts were observed in 4% cases each. 2% cases exhibited abnormal low fusion of cystic duct with common hepatic duct. Conclusions: These anomalies may add to postoperative complications if ignored. Present study is a step in the direction of creating awareness about these variations among the clinicians.